О morskiej „voyage de noce” („Nа «Tytaniku»” Мichaiła Zienkiewicza) - Kulikowa, Elena (Studia Rossica Posnaniensia, 2012)
Yelena Kulikova’s paper “On a Sea Voyage de Noce (M. Zenkevich’s On the «Titanic»)” analyzes Mikhail Zenkevich’s poem about the demise of the famous ship against the background of Dante’s Divine Comedy. The author notes the Acmeist approach in Zenkevich’s description of the Titanic where the object crafted by the hands of a human creator becomes alive. The sea voyage de noce of the protagonists is interrupted by the destruction of the Titanic and turns into a journey through the circles of Hell, while Helène becomes a double for Beatrice and, like Dante’s heroine, saves the protagonist’s soul.